Numerical Analyses of Fracturing Behavior and Strength of Specimens with Two Parallel Infilled Flaws under Uniaxial Compression - Huilin Le; Jihong Wei; Shaorui Sun; Wuchao Wang; Haotian Fan (Advances in Civil Engineering)
Grouting is a common method used to fill rock joints to improve the stability and integrity of rock mass in geotechnical engineering, and the filling has been observed to have an effect on crack behavior and mechanical property. To investigate this topic, a numerical study of crack behavior and mechanical property of rock samples with two parallel open flaws or infilled flaws under uniaxial compression was conducted in this research. The smooth joint model was proved to be suitable to simulate the interface between rock material and grout material. The occurrence of shear cracks at the interface between rock material and grout material as well as the occurrence of tensile cracks in the grouting material has been successfully simulated in this research. Numerical results indicate that grouting can reduce the tensile force near the flaws, suppress the generation of tensile cracks, and improve the initiation stress of the sample. The tensile force in the specimens with infilled flaws is smaller than that with open flaws, which lead to the improvement of the peak strength of the sample. Moreover, crack development and mechanical properties of samples are affected by bridge inclination angle and flaw inclination angle.